2015
DOI: 10.4103/0974-620x.159270
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ophthalmic artery occlusion in children due to Hyperhomocysteinemia

Abstract: Ophthalmic artery occlusion usually presents as a sudden onset profound decrease in vision in the middle-aged and elderly patients following periocular procedures (retrobulbar injection/glabellar fat injection), embolism from the heart or after prolonged systemic surgery. In this report, we describe three children with spontaneous ophthalmic artery occlusion who presented with unilateral loss of vision and diagnosed elsewhere as optic atrophy whose detailed history and examination were suggestive of ophthalmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Attenuation of only retinal arterioles has been reported following BRAO [33], CRAO [34], and central retinal vein occlusion (CRVO) [35]; whereas combined arteriolar/venular attenuation has been noted following ophthalmic artery occlusion [36] and BRVO [37].…”
Section: A Note Regarding Retinal Vascular Attenuationmentioning
confidence: 99%
“…Attenuation of only retinal arterioles has been reported following BRAO [33], CRAO [34], and central retinal vein occlusion (CRVO) [35]; whereas combined arteriolar/venular attenuation has been noted following ophthalmic artery occlusion [36] and BRVO [37].…”
Section: A Note Regarding Retinal Vascular Attenuationmentioning
confidence: 99%
“…Развитие окклюзии ЦАС в молодом возрасте может быть связано с гипергомоцистеинемией [84] и с повышенным значением ET-1в плазме крови, что характерно для лиц, страдающих первичной сосудистой дисрегуляцией и эндотелиальной дисфункцией [33].…”
Section: эндотелиальная дисфункция и окклюзия ветвиunclassified
“…OAO is rare, comprising 2% of all ocular vascular occlusions and most commonly affects middle age to elderly patients with cardiovascular disease (1). Cases of OAO in the pediatric population have been reported, most due to prolonged surgery, periocular injections, embolic phenomena, and hyperhomocysteinemia (2). To the authors knowledge, there has not been a reported case in the setting of FCA.…”
mentioning
confidence: 99%
“…The better than anticipated vision was possibly due to a patent cilioretinal artery system, which is present in approximately 36% of the general population (3). Although the presence of a cherry red spot is characteristic of CRAO, it can be present in OAO if the choroidal circulation recovers, even partially (2). Partial choroidal recovery may also have contributed to our patient’s relatively good vision.…”
mentioning
confidence: 99%